Evaluation of organizational resources for innovation in midsize Brazilian company - da Costa, Priscila Rezende; Pagan Martínez, Marta [UNESP]; Itelvino, Lucimar da Silva (My University, 2016)
Structuring an overview of the innovation stages and the analysis of potentiate organizational resources of innovative solutions are essential not only for understanding the innovator behavior of midsize companies, but for rising issues that may be useful for public policies to support innovation in the Brazilian average company. Given this background, the article sought to map the innovative profile of midsize companies. The results are shown and discussed in three topics: (a) the proposition of generic stages for innovation, (b) the characterization of midsize businesses and their innovation stages, and (c) interference of organizational resources in the innovation stages in these companies.
Keywords: Innovation stages; Midsize companies; Organizational resources